A Merged Search‐Coil and Fluxgate Magnetometer Data Product for Parker Solar Probe FIELDS. Issue 5 (9th May 2020) - Bowen, T. A.; Bale, S. D.; Bonnell, J. W.; Dudok de Wit, T.; Goetz, K.; Goodrich, K.; Gruesbeck, J.; Harvey, P. R.; Jannet, G.; Koval, A.; MacDowall, R. J.; Malaspina, D. M.; et al.
Abstract: NASA's Parker Solar Probe (PSP) mission is currently investigating the local plasma environment of the inner heliosphere (<0.25 R ⊙ ) using both in situ and remote sensing instrumentation. Connecting signatures of microphysical particle heating and acceleration processes to macroscale heliospheric structure requires sensitive measurements of electromagnetic fields over a large range of physical scales. The FIELDS instrument, which provides PSP with in situ measurements of electromagnetic fields of the inner heliosphere and corona, includes a set of three vector magnetometers: two fluxgate magnetometers (MAGs) and a single inductively coupled search‐coil magnetometer (SCM). Together, the three FIELDS magnetometers enable measurements of the local magnetic field with a bandwidth ranging from DC to 1 MHz. This manuscript reports on the development of a merged data set combining SCM and MAG (SCaM) measurements, enabling a high fidelity data product with an optimal signal‐to‐noise ratio. On‐ground characterization tests of complex instrumental responses and noise floors are discussed as well as application to the in‐flight calibration of FIELDS data. The algorithm used on PSP/FIELDS to merge waveform observations from multiple sensors with optimal signal‐to‐noise characteristics is presented. In‐flight analysis of calibrations and merging algorithm performance demonstrates a timing accuracy to well within the survey rate sample period of ∼340 μs. Key Points: We develop a technique to merge search‐coil and fluxgate magnetometer measurements In‐flight analysis shows that calibrations are accurate to within 100 μs